Ag-Mo modified SCR catalyst for a co-beneficial oxidation of elemental mercury at wide temperature range. (15th July 2017) - Zhao, Songjian; Xu, Haomiao; Mei, Jian; Ma, Yongpeng; Lou, Tong; Qu, Zan; Yan, Naiqiang
Graphical abstract: Highlights: V-Mo-Ti was more active than V-W-Ti for the catalytic oxidation of elemental mercury. The dope of Ag can improve markedly the mercury oxidation efficiency of V-Mo-Ti. The catalytic mechanisms were different at various temperature ranges. Abstract: V2 O5 -MoO3 -TiO2 (V-Mo-Ti) is often used as a selective catalytic reduction catalyst for NOx from coal-fired flue gas. The performance of a V-Mo-Ti catalyst for the oxidation of elemental mercury (Hg 0 ) was investigated. It was found that Mo was resistant toward sulfur dioxide and can enhance the Hg 0 adsorption capacity. Ag was employed to enhance the Hg 0 oxidation reaction and can enlarge reaction temperature window. Doping with Ag can significantly enhance the oxidation of Hg 0, and adding only 0.5% Ag can keep Hg 0 oxidation efficiency to approximately 90% with 5 ppm HCl, with an increase of 20–40% compared to that of V-Mo-Ti catalyst. Besides, the reaction temperature window of catalyst was enlarged from 150 to 400 °C. TEM and XPS characterization data indicated that Ag nanoparticles were loaded on the Mo/V-Ti carrier, maintaining Ag-Mo/V-Ti at a higher oxidation state. Furthermore, the TPR and Deacon reaction tests suggested that the Ag dopant might enhance the redox behavior, which facilitates the Deacon or semi-Deacon reactions for HCl activation. In addition, Hg 0 desorption and breakthrough experiments and mercury valence state change experiments were carried out to investigate the Hg 0 catalytic oxidation mechanisms at various temperature ranges.